Impact of Tempering Factors on Mechanical Properties of Ck55 Steel (0.55wt%C - 0.75wt%Mn) - R. Biswal, S.; T. Nayak, S. (International Journal of Engineering and Technology, 2018)
In the composite era, steel have been still gaining emphasis for automobile machine parts. In this regard Ck55 steel is taken due to its optimum balance between ductility and strength in tempered conditions. In present study, Ck55 grade steel is tempered at three temperature conditions i.e. at 6000C, 4000C and 2000C for different time length. The properties of all the specimens are evaluated and we found the maximum hardness and tensile strength for tempering at 2000C for 1 hour with minimum ductility because of the presence of less no. of softer carbide and ferrite. We get the maximum ductility at tempering at 6000C for 2 hours with minimum tensile strength because softer carbide and ferrite dominants whole of the microstructure. It is found that tempering time and temperature greatly influences the strength as well as hardness value without much compromise in the ductility. Â Â Â